Epidemiological and clinical profile of patients with attempted suicide seen at a psychiatric referral hospital (Research, Society and Development, 2020)
This study aims to outline the epidemiological and clinical profile of patients with attempted suicide admitted to a psychiatric reference hospital in the State of Pará. This is a retrospective observational epidemiological study with a quantitative-descriptive approach, performed on 28 patient records admitted to a Psychiatric Clinic in Belém-Pará, diagnosed with attempted suicide. Data analysis was performed using descriptive statistics and the Chi-square test. The results show that the incidence rate calculated for suicide attempt was 101 / thousand patients, 57% of the patients were female and 43% were male; 32.0% were between 19 and 24 years old and 36.0% between 25 and 34 years old; 53.6% had incomplete / complete elementary school; 82.1% were single and 46.4% were unemployed / unemployed. The main means used for the act were self-mutilation (22%), hanging (14%) and drowning (14%); all were diagnosed with some mental disorder, the most frequent of which were: unspecified non-organic psychosis (61%) and schizophrenia (18%); The main reasons identified were: refusal of treatment (43%), serious family disorders (14%) and lack of medication in the public health system (11%), where all patients analyzed offered some risk of committing another suicide attempt . The results are in line with data from the literature on the subject and point out that individuals who attempt against their own lives have very heterogeneous characteristics and may be in the most different social classes.